EL LADO OSCURO DEL 3: EN PAREMIAS Y FRASEO-LOGISMOS DEL ESPAÑOL Y DEL GRIEGO* - Álvarez, Carlos Alberto Crida (Proverbium - Yearbook, 2014)
In several European languages concepts that express something positive or negative by the cardinal numeral three or the ordinal third or even by a triad have been fixed in proverbs and idioms. This article focuses on the negative side only of this figure, as diachronically appears in Spanish and Greek languages, without discarding other European languages. We believe that the negative feature of the number three has its cultural origins in the Greco-Roman world, and more specifically in Greek mythology, and that its transmission would be done through the Jungian “collective unconscious.” The negative symbolism of this figure would be the source of some metaphors, which would have been fixed in phraseological units.